Understanding recovery of language after stroke: insights from neurovascular MRI studies - Ivanova, Maria V.; Pappas, Ioannis (Frontiers in Language Sciences, 2023)
Stroke causes a disruption in blood flow to the brain that can lead to profound language impairments. Understanding the mechanisms of language recovery after stroke is crucial for the prognosis and effective rehabilitation of people with aphasia. While the role of injured brain structures and disruptions in functional connectivity have been extensively explored, the relationship between neurovascular measures and language recovery in both early and later stages has not received sufficient attention in the field. Fully functioning healthy brain tissue requires oxygen and nutrients to be delivered promptly via its blood supply. Persistent decreases in blood flow after a stroke to the remaining non-lesioned tissue have been shown to contribute to poor language recovery. The goal of the current paper is to critically examine stroke studies looking at the relationship between different neurovascular measures and language deficits and mechanisms of language recovery via changes in neurovascular metrics. Measures of perfusion or cerebral blood flow (CBF) and cerebrovascular reactivity (CVR) provide complementary approaches to understanding neurovascular mechanisms post stroke by capturing both cerebral metabolic demands and mechanical vascular properties. While CBF measures indicate the amount of blood delivered to a certain region and serve as a proxy for metabolic demands of that area, CVR indices reflect the ability of the vasculature to recruit blood flow in response to a shortage of oxygen, such as when one is holding their breath. Increases in CBF during recovery beyond the site of the lesion have been shown to promote language gains. Similarly, CVR changes, when collateral vessels are recruited to help reorganize the flow of blood in hypoperfused regions, have been related to functional recovery post stroke. In the current review, we highlight the main findings in the literature investigating neurovascular changes in stroke recovery with a particular emphasis on how language abilities can be affected by changes in CBF and CVR. We conclude by summarizing existing methodological challenges and knowledge gaps that need to be addressed in future work in this area, outlining a promising avenue of research.